Planning, Implementing, and Maintaining a Microsoft Windows® Server™ 2003 Environment Exam Cram™ 2 (Exam 70-296) - Schmied, Will (Que, 2011)
Welcome to the 70-296 Exam Cram 2! Whether this is your first or your fifteenth Exam Cram 2 series book, you'll find information here that will help ensure your success as you pursue knowledge, experience, and certification. This introduction explains Microsoft's certification programs in general and talks about how the Exam Cram 2 series can help you prepare for the Microsoft Certified Systems Engineer and Microsoft Certified Systems Administrator exams. Chapter 1, "Microsoft Certification Exams," discusses the basics of Microsoft certification exams, including a description of the testing environment and test-taking strategies. Chapters 2–10 are designed to remind you of everything you'll need to know to take—and pass—the 70-296 exam. The two practice exams at the end of the book should give you a reasonably accurate assessment of your knowledge—and, yes, we've provided the answers and their explanations to the tests. Read the book and understand the material, and you'll stand a very good chance of passing the test.